Consideration of the Management of Pediatric Fever Clinics During the Novel Coronavirus Pneumonia Outbreak. (12th December 2021) - Ding, Hui; Shi, Zhaoling; Ruan, Zhen; Cheng, Xiaoning; Li, Ruying; Zhang, Lu; Han, Xuanming; Zhang, Zhihong; Gao, Nairong; Guo, Yanzi; Zhang, Meng; Ma, Wenjuan; et al.
ABSTRACT: Since the outbreak of 2019 novel coronavirus (2019-nCoV) infection in Wuhan City, China, pediatric cases have gradually increased. It is very important to prevent cross-infection in pediatric fever clinics, to identify children with fever in pediatric fever clinics, and to strengthen the management of pediatric fever clinics. According to prevention and control programs, we propose the guidance on the management of pediatric fever clinics during the nCoV pneumonia epidemic period, which outlines in detail how to optimize processes, prevent cross-infection, provide health protection, and prevent disinfection of medical staff. The present consideration statement summarizes current strategies on the pre-diagnosis, triage, diagnosis, treatment, and prevention of 2019-nCoV infection, which provides practical suggestions on strengthening the management of pediatric fever clinics during the nCoV pneumonia epidemic period.